BRAND COMMITMENT DAN BRAND PSYCHOLOGICAL OWNERSHIP DALAM MEMEDIASI PENGARUH INTERNAL CORPORATE BRANDING TERHADAP BRAND CITIZENSHIP BEHAVIOR - Agus Purnomo (Universitas Mercu Buana, 2019)
This study examined the influence of internal corporate branding on brand citizenship behavior. Research conduct on leading telecommunications services companies in the city of Malang. The results show that internal corporate branding has a positive and significant effect on brand citizenship behavior. Internal corporate branding also has a positive and significant effect on brand commitment and brand psychological ownership. Brand commitment and brand psychological ownership mediate relationship internal corporate branding to brand citizenship behavior, as well as directly each variable has a positive and significant influence on brand citizenship behavior.